STOCHASTIC DEMAND IN VEHICLE ROUTING PROBLEM WITH COMPARTMEN - Normasari, Nur Mayke Eka; Warangga, Anjas Fikhri; Nugrahandika, Widyasari Her (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
This research focus on consideration of stochastic demand in deterministic Vehicle Routing Problem with Compartment (VRPC) model. VRPC in this research consider split delivery, multi product, and time windows characteristic. Stochastic demand in this research is handled using scenario-based approach. The demand is modeled by constructing discrete scenarios then implementing it in the deterministic VRPC model. The change of customer demand over time is considered as normal probability distribution. Stochastic VRPC model then solved using robust approach by looking for the highest demand under each scenario to be solve, therefore the solution generated deals with the minimum probability of unmet demand.